UPAYA PENINGKATAN AKTIVITAS SISWA DALAM KEDUDUKAN DAN FUNGSI PANCASILA MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI SMP NEGERI 3 MUARA BUNGO - nurhayati nurhayati (Jurnal Tunas Pendidikan, 2021)
This research is motivated by the activities of students in Civics learning that are still less active and participating because there is only giving information from teachers to students so that students are less enthusiastic and look bored during the learning process. This study aims to increase student citizenship education activities through a contextual teaching and learning approach to class IX.1 students in the even semester of the 2019/2020 school year at SMP Negeri 3 Muara Bungo. This type of research is classroom action research (CAR) with a qualitative descriptive approach carried out in two cycles of four stages, namely planning, implementation, observation, and reflection. The indicators used are the ability to answer questions, the courage to ask questions, express opinions, the skills to give suggestions, and come up with conclusions. The results showed an increase in each indicator in the first cycle compared to the initial observations, namely 5.3%, 7%, 2.6%, 2.6%, 7.9%. while the increase in the second cycle compared to the first cycle, namely 5.2%, 2.6%, 2.6%, 5.2%, 2.6%. it can be concluded that student activity in Civics learning can be increased by using the Contextual Teaching and Learning approach at SMP Negeri 3 Muara Bungo.